Construction of an Artificial Ferrimagnetic Lattice by Lithium Ion Insertion into a Neutral Donor/Acceptor Metal–Organic Framework. Issue 17 (16th March 2016) - Taniguchi, Kouji; Narushima, Keisuke; Mahin, Julien; Kosaka, Wataru; Miyasaka, Hitoshi
Abstract: Construction of a molecular system in which the magnetic lattice exhibits long‐range order is one of the fundamental goals in materials science. In this study, we demonstrate the artificial construction of a ferrimagnetic lattice by doping electrons into acceptor sites of a neutral donor/acceptor metal–organic framework (D/A‐MOF). This doping was achieved by the insertion of Li‐ions into the D/A‐MOF, which was used as the cathode of a Li‐ion battery cell. The neutral D/A‐MOF is a layered system composed of a carboxylate‐bridged paddlewheel‐type diruthenium(II, II) complex as the donor and a TCNQ derivative as the acceptor. The ground state of the neutral form was a magnetically disordered paramagnetic state. Upon discharge of the cell, spontaneous magnetization was induced; the transition temperature was variable. The stability of the magnetically ordered lattice depended on the equilibrium electric potential of the D/A‐MOF cathode, which reflected the electron‐filling level. Abstract : A ferrimagnetic order lattice has been artificially constructed by electron doping by lithium ion insertion from a magnetically disordered ground state in a neutral donor/acceptor metal–organic framework (D/A‐MOF). The stability of the magnetically ordered lattice depends on the equilibrium potential of the D/A‐MOF cathode. The results suggest a new strategy and direction for the design of molecule‐based magnets.